A critical analysis on the adjudication process of dismissal under section 20 of the Industrial Relations Act 1967 / Muhammad Aizat Abd. Rahim ... [et al.] - Abd. Rahim, Muhammad Aizat; Syed Mokhtar, Syed Ahmad Oraif; Zainal, Amir Hamzah; Mohd Dzulkaflee, Muhamad Wafi (2011)
One of the trade dispute relating to the industrial relations, is involving unlawful dismissal. Thus, based on section 20 of the Industrial Relations Act (IRA), the provision itself provides the guidelines for the aggrieved workman to seek for reinstatement. Therefore, this raises a question whether the guidelines or procedure provided is effective or not in handling the arising numbers of trade disputes. Hence, this research will examine the effectiveness and also the defects of the guidelines or procedures provided by the provision. Apart from that, this research will also examine the alternative procedure which might be appropriate to be use to rectify the defect of the current procedure. Findings showed that the guidelines or procedures provided by the provision do have their own defects in handling the arising numbers of trade disputes. It is also hoped that this research can be a useful guidelines to the concerned parties (especially to the government) to review the existing provisions in order to provide new provisions and guidelines so that that the guidelines or procedures can be much more effective in settling the arising numbers of trade disputes especially involving unlawful dismissal in the near future.